Hypnea musciformis (Cystocloniaceae) from the Yucatan Peninsula: morphological variability in relation to life-cycle phase. Issue 2 (1st March 2016) - Vázquez-Delfín, Erika; Boo, Ga Hun; Rodríguez, Dení; Boo, Sung Min; Robledo, Daniel
Abstract: Hypnea musciformis is one of the most studied species of the genus Hypnea . It has a wide geographic range along the Atlantic, Pacific and Indian Oceans that would be consistent with an extensive intraspecific variation in morphology. Hypnea musciformis has been previously reported on coasts of the Yucatan Peninsula; however, neither morphological characterization nor molecular studies have been done for Gulf of Mexico or Mexican Caribbean populations. For the first time, we present a detailed morphoanatomical description of the tetrasporophytic, gametophytic and carposporophytic phases and its reproductive structures for this region, including the description of the male gametophyte. Mexican Caribbean samples showed morphological variation in branching pattern, branch abundance and branchlet types, and this was attributed to life-history phase and the reproductive status of the thalli. Molecular analysis of ribulose-1, 5-bisphosphate carboxylase/oxygenase gene and the 5′ region of the mitochondrial cytochrome C oxidase subunit I gene markers allows us to confirm the unique genetic identity of Mexican specimens. The analysis of H. musciformis collected in different tropical areas showed a high degree of intraspecific variation and suggested the necessity of a combined analysis of morphology and different gene markers for a better understanding of its taxonomy and phylogeny.